2017
DOI: 10.1186/s13071-017-2429-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oral moxidectin against susceptible and resistant isolates of Dirofilaria immitis in dogs

Abstract: BackgroundMonthly topical and sustained-release injectable formulations of moxidectin are currently marketed; however, an oral formulation, while approved at a dose of 3 μg/kg, is not currently marketed in the United States. Although resistance of heartworms to all macrocyclic lactone (ML) heartworm preventives (ivermectin, milbemycin, selamectin and moxidectin) has been demonstrated, to date no data have been reported on the effectiveness of oral moxidectin against recent isolates of Dirofilaria immitis.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 8 publications
0
42
0
Order By: Relevance
“…This in turn will be influenced by the route of administration; different preparations, one topical, the other a long-lasting injectable were used by Blagburn et al (2016) and Bourguinat et al (2015) respectively. McTier et al (2017) reported that JYD-34 was resistant to oral administration of moxidectin. In small ruminants the use of moxidectin to control ivermectin-resistant nematodes resulted in the rapid development of moxidectin resistance (Kaplan et al, 2007) which suggests that the use of moxidectin-based preventatives will provide only a short-term solution, if any.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn will be influenced by the route of administration; different preparations, one topical, the other a long-lasting injectable were used by Blagburn et al (2016) and Bourguinat et al (2015) respectively. McTier et al (2017) reported that JYD-34 was resistant to oral administration of moxidectin. In small ruminants the use of moxidectin to control ivermectin-resistant nematodes resulted in the rapid development of moxidectin resistance (Kaplan et al, 2007) which suggests that the use of moxidectin-based preventatives will provide only a short-term solution, if any.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting accounts of the efficacy of moxidectin as a preventative against these resistant worms, which may reflect the dose of drug the parasite is exposed to following different routes of administration. One resistant isolate, JYD-34, was reported to remain susceptible to topically applied moxidectin (Blagburn et al, 2016), in that no adult worms were present at necropsy following experimental infection with infective L3 larvae and treatment, but to be resistant to either one or three oral doses (3 μg/kg) of the drug (McTier et al, 2017). Another isolate, Jd2009-2, was fully resistant to a long-acting injectable formulation of the drug given 6 months after infection (Bourguinat et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Both isolates were validated as infective strains through the diagnosis of circulating microfilariae, positive heartworm antigen test results, and adult worm recovery in recipient animals following inoculation of L 3 that had been derived directly from microfilariae obtained from the original field cases. Both ZoeLA and JYD-34 D. immitis strains have been demonstrated to be resistant to MLs [4,10].…”
Section: Dirofilaria Immitis Strainsmentioning
confidence: 99%
“…To provide reliable efficacy against this stage, pyrantel is needed in the combination. Moxidectin at a single oral dose of 3 µg/kg was shown to be effective against susceptible Dirofilaria immitis isolates [29], and more recent studies have confirmed its efficacy in the prevention of canine heartworm (L 4 stages) and lungworm (L 5 stage) disease at 24 µg/ kg in combination with pyrantel and sarolaner [30,31]. The dosage of moxidectin in Simparica Trio ™ has been selected in dose titration studies against these vascular nematodes [31,32].…”
Section: Clinical Benefits Of the Combination Productmentioning
confidence: 99%